Halo-hydromorphism alters nitrogen fertilization responses of tall wheatgrass pastures: Capture and use of resources, tiller dynamics and forage production - Fina, Federico; Bertram, Nicolas; Gatti, María Laura; Di Bella, Carla Estefania; Grimoldi, Agustin Alberto; Berone, German Dario (Wiley, 2024)
Halo-hydromorphism limits productivity in approximately 100 million hectares worldwide. Tall wheatgrass (Thinopyrum ponticum) is a species widely used in these environments for its seeding potential, being the addition of nitrogen a considered technological tool to increase forage quality and production. The objective of the study was to determine the impact of nitrogen fertilization on the capture and use of resources (radiation, water and nitrogen) in a cool season perennial sward growing in contrasting halo-hydromorphic conditions. Cultivated pastures from three independent sites were used. Sites were described according to the degree of halo-hydromorphism using soil salinity and water table attributes (salinity and depth) as environmental indicators: low HHM site [electrical conductivity (EC1:2.5) 0.97 dS/m; water table salinity 2.03 dS/m; depth 85 cm], intermediate HHM site (EC1:2.5 3.86 dS/m; water table salinity 7.40 dS/m; depth 134 cm) and high HHM site (EC1:2.5 4.49 dS/m; water table salinity 7.85 dS/m; depth 31 cm). At each site, a late spring regrowth (~750°Cd) was studied by applying two treatments (n = 5): without (N0) and nitrogen fertilization (N150; 150 kg/ha of nitrogen in the form of urea). The response of tall wheatgrass to nitrogen fertilization in halo-hydromorphic conditions depends on soil salinity and water table attributes. N150 treatments production was twice as high as in N0 in low HHM and intermediate HHM environments (from 1750 to 3500 kgDM/ha and from 1080 to 1985 kgDM/ha, respectively). Meanwhile, in high HHM conditions, forage production was only 40% higher when nitrogen was added (from 625 to 870 kgDM/ha). In low HHM the higher N150 production was related to tiller density and size, whereas in intermediate HHM and high HHM was linked only to tiller size. In N150 treatments, the nitrogen nutrition index was negatively affected with the increase in HHM conditions (0.77, 0.62 and 0.55 for low HHM, intermediate HHM and high HHM, respectively). Instead, nitrogen nutrition index of N0 was similar in all the environments (~0.42). In N150, forage production capacity analysed in terms of radiation and water use efficiency (RUE and WUE, respectively) was similar in low HHM and intermediate HHM environments (RUE ~0.81 gDM/Mj and WUE ~13 kgDM/mm). These findings emphasize the importance of conducting analyses based on resource use and capture to understand productive responses to the increase in growth-limiting factors. Furthermore, they contribute to the identification of environments suitable for nitrogen fertilization.